Enhancing medical intern competence in urethral catheterization: Impact of simulation-based training on knowledge, self-efficacy, and clinical outcomes - Maher Abdessater; Anthony Kanbar; Joey El Khoury; Rami Halabi; Ramy Touma Sawaya; Raghid El Khoury (PLoS ONE, 2026)
Introduction Urethral catheterization is a common procedure, yet most related complications occur when performed by new medical interns. Studies have shown inadequate training and knowledge among junior doctors. This study evaluated the declarative knowledge of new interns regarding urethral catheterization and assessed the effectiveness of a simulation-based urology session in improving their knowledge, confidence, and perceived self-efficacy. Methods A one-day urology simulation workshop was conducted for 40 new interns at a university hospital. Participants completed a pre-session online questionnaire assessing demographics, urinary catheterization knowledge, and self-reported confidence and self-efficacy. The workshop included three modules: an interactive presentation, instructional videos, and hands-on simulation on male and female models. Post-session assessments measured changes in knowledge, confidence, and self-efficacy scores using standardized evaluation tools. Results Forty new medical interns participated. Only 15% felt adequately prepared before training. Knowledge gaps were identified regarding catheter types and sizes (92.5%), optimal patient positioning (62%), proper meatus exposure, and balloon inflation technique (100%). Following the workshop, mean knowledge scores increased from 7.7 ± 1.24 to 12.2 ± 1.11, self-reported confidence from 6.60 ± 1.79 to 8.66 ± 0.94, and perceived self-efficacy from 3.32 ± 0.94 to 4.32 ± 0.62 (all p < 0.001). At six-month follow-up, participants collectively performed 274 urethral catheterizations with a 93% success rate and a low complication rate of 4% (n = 11), reflecting effective transfer of learning from the simulation to clinical practice. Discussion New medical interns demonstrated insufficient baseline knowledge of urethral catheterization. The structured urology simulation session significantly improved their declarative knowledge, confidence, and perceived self-efficacy, underscoring the value of simulation-based training in early postgraduate medical education.